International maritime law and practice : comparative law in context - Pejovic, Caslav (Routledge, 2025)
"This book provides a different perspective on the ever-popular topic of maritime law, emphasising historical and comparative aspects. It provides the reader with a broader view of how maritime law has developed throughout history and operates within various legal systems. Each chapter starts with historical development, meticulously explaining the development of various maritime law concepts to enable a higher level of understanding in the contemporary context. The text adopts a comprehensive comparative approach that has two segments. One segment is related to the coverage of several major maritime jurisdictions. Focusing mainly on English law, it also provides selected legislation and essential case law information from several other jurisdictions (US, France, Germany, Italy, Japan, China, etc), many of which are not easily accessible in English. The other relates to the comparison between common law and civil law on a general level. This book will be of significant interest to lawyers working in shipping companies, law firms specializing in shipping, international organizations related to shipping and maritime law, and international traders. It also provides invaluable aid to shipmasters and ship officers, empowering them with the knowledge to effectively deal with various maritime law issues in their professional activities. The book's content will be of direct relevance to maritime law scholars and students, enhancing their understanding of this complex field"-- Provided by publisher.
Keywords: Maritime law -- History.; Shipbuilding contracts.; Ship mortgages.; elektronické knihy; electronic books